Electrical stimulation of coleopteran muscle for flight cessation - Tnee, Chin Kiat (2016)
The aim of this report is to demonstrate the study of insect flight control on the anatomical level study of the musculature structure of the beetle and also studying the flight style of the beetle with the aid of motion capture technology.